2023
DOI: 10.1002/adfm.202214357
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Thermally Stable Wide Bandgap Perovskite Solar Cells by Dual‐Source Vacuum Deposition

Abstract: Wide bandgap perovskites are being widely studied in view of their potential applications in tandem devices and other semitransparent photovoltaics. Vacuum deposition of perovskite thin films is advantageous as it allows the fabrication of multilayer devices, fine control over thickness and purity, and it can be upscaled to meet production needs. However, the vacuum processing of multicomponent perovskites (typically used to achieve wide bandgaps) is not straightforward, because one needs to simultaneously con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…In general, spin-coating processes using nonvolatile polar solvents, such as dimethyl sulfoxide (DMSO) and N,N -dimethyl­formamide (DMF), are used to fabricate highly efficient PVSK films for multijunction devices. , These solvents readily penetrate the interfacial layers between two PVSK films during the second spin-coating process, leading to the partial dissolution of the underneath PVSK layer . It was also reported that the residual nonvolatile solvents still exist in the thin film even after the drying process due to the formation of a PVSK–solvent intermediate phase. , Depositing a dense oxide interlayer via atomic layer deposition (ALD) is a proven way to prevent the degradation of the underneath PVSK layer. However, the ALD process with a slow growth rate requires a long process time, potentially increasing the fabrication cost and causing damage to the PVSK cell due to the oxidizing agent and the high process temperature. Another way to avoid the solvent-related degradation of the underneath PVSK layer is to adopt vacuum deposition techniques, , but no study has so far demonstrated the successful vacuum deposition of an upper PVSK layer on another PVSK layer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, spin-coating processes using nonvolatile polar solvents, such as dimethyl sulfoxide (DMSO) and N,N -dimethyl­formamide (DMF), are used to fabricate highly efficient PVSK films for multijunction devices. , These solvents readily penetrate the interfacial layers between two PVSK films during the second spin-coating process, leading to the partial dissolution of the underneath PVSK layer . It was also reported that the residual nonvolatile solvents still exist in the thin film even after the drying process due to the formation of a PVSK–solvent intermediate phase. , Depositing a dense oxide interlayer via atomic layer deposition (ALD) is a proven way to prevent the degradation of the underneath PVSK layer. However, the ALD process with a slow growth rate requires a long process time, potentially increasing the fabrication cost and causing damage to the PVSK cell due to the oxidizing agent and the high process temperature. Another way to avoid the solvent-related degradation of the underneath PVSK layer is to adopt vacuum deposition techniques, , but no study has so far demonstrated the successful vacuum deposition of an upper PVSK layer on another PVSK layer.…”
mentioning
confidence: 99%
“…24−26 However, the ALD process with a slow growth rate requires a long process time, potentially increasing the fabrication cost and causing damage to the PVSK cell due to the oxidizing agent and the high process temperature. 27−29 Another way to avoid the solvent-related degradation of the underneath PVSK layer is to adopt vacuum deposition techniques, 30,31 but no study has so far demonstrated the successful vacuum deposition of an upper PVSK layer on another PVSK layer. This study used a novel solvent mixture of acetonitrile (ACN) and methylamine (MA) in ethanol with higher volatility than conventional solvent mixtures to prevent the degradation of the PVSK bottom cell during the processing of another PVSK top cell.…”
mentioning
confidence: 99%
“…Commercial PERC solar cells with 23.4% efficiency were utilized and the semitransparent/ PERC c‐Si 4T tandem device power output was obtained by PD IEC TS 60904‐1‐2 and the calculation method was provided in supporting information. [ 35 ] In addition to the 23.3% efficiency produced by the ST‐PSCs, the filtered PERC solar cell generated 7.5% efficiency (Figure S17, Supporting Information), totaling the output power is 30.8 mW cm −2 , which is among the highest of the 4‐T perovskite/PERC‐Si tandem solar cells (Table S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a short annealing process of 100 °C for 2 min noticeably improved device performance (Figure S7) and may point to the feasibility of shorter annealing times for improving device performance. Despite this, a prolonged annealing at 85 °C was chosen for this study to compare with an existing baseline for thermal stressing of perovskite solar cells in our group . Device stability and performance were tracked for a total of 650 h. In Figure a, the notable increase in PCE occurs over the first 200 h and is reflected in the FF, J sc , and V oc where trend lines have been marked.…”
Section: Organic Source Reusability and Thin-film Propertiesmentioning
confidence: 99%
“…Despite this, a prolonged annealing at 85 °C was chosen for this study to compare with an existing baseline for thermal stressing of perovskite solar cells in our group. 31 Device stability and performance were tracked for a total of 650 h. In Figure 4 a, the notable increase in PCE occurs over the first 200 h and is reflected in the FF, J sc , and V oc where trend lines have been marked. In particular, the V oc improved from 0.8 to 1.04 V over 9 days of thermal stressing.…”
Section: Device Stabilitymentioning
confidence: 99%